Pengembangan Model Pembelajaran Inovatif Berbasis Mobile Learning pada Pembelajaran Menulis Karangan untuk Siswa SMP Kelas VIII di Kabupaten Brebes - Hany Uswatun Nisa; Didik Tri Setiyoko; Yasin Yasin; Novi Yuliyanti (Journal on Education, 2023)
The purpose of this study is to develop an innovative Mobile Learning-based instructional model for essay writing in the eighth grade of SMP students and to determine the feasibility of the developed product in the form of an innovative Mobile Learning-based instructional model for essay writing in the eighth grade of SMP students in Brebes Regency. This research utilizes the development model adapted from the ADDIE model. The results of this application development consist of four stages: analysis, design, development, and implementation. The product's feasibility test for users was conducted on 30 students from SMP N 1 Ketanggungan and 30 students from SMP N 2 Banjarharjo. The results of the feasibility test proved that the M-Learning product is suitable for use in both schools. This is evidenced by the significance score obtained from the t-test, which is greater than the applied alpha score (0.05), namely 0.124 for SMP N 1 Ketanggungan, and the significance score obtained from the t-test is also greater than the applied alpha score (0.05), namely 0.102 for SMP N 2 Banjarharjo. Keywords: m-Learning, Writing, Description.